2018
DOI: 10.3390/nu10060660
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blinded, Placebo-Controlled Study to Compare the Safety and Efficacy of Low Dose Enhanced Wild Blueberry Powder and Wild Blueberry Extract (ThinkBlue™) in Maintenance of Episodic and Working Memory in Older Adults

Abstract: Previous research has shown beneficial effects of polyphenol-rich diets in ameliorating cognitive decline in aging adults. Here, using a randomized, double blinded, placebo-controlled chronic intervention, we investigated the effect of two proprietary blueberry formulations on cognitive performance in older adults; a whole wild blueberry powder at 500 mg (WBP500) and 1000 mg (WBP1000) and a purified extract at 100 mg (WBE111). One hundred and twenty-two older adults (65–80 years) were randomly allocated to a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 41 publications
7
118
0
1
Order By: Relevance
“…Numerous studies have focused on the impact of blue berries, citrus fruit and green tea on human health. It was proved that blueberry extract is able to significantly improve episodic memory and visuospatial working memory as a result of three-months supplementation and can also reduce systolic blood pressure level already after three-months supplementation [61]. A recent study by Bell and Williams [62] demonstrated a significant positive influence of honeysuckle berry extract on physiological and cognitive functions in the immediate postprandial period.…”
Section: Neuroprotective Activitymentioning
confidence: 98%
“…Numerous studies have focused on the impact of blue berries, citrus fruit and green tea on human health. It was proved that blueberry extract is able to significantly improve episodic memory and visuospatial working memory as a result of three-months supplementation and can also reduce systolic blood pressure level already after three-months supplementation [61]. A recent study by Bell and Williams [62] demonstrated a significant positive influence of honeysuckle berry extract on physiological and cognitive functions in the immediate postprandial period.…”
Section: Neuroprotective Activitymentioning
confidence: 98%
“…These (poly)phenol compounds (i.e., flavones, flavonols, isoflavones, flavanones/flavanonols, flavanols, and anthocyanidins) are present in high amounts in fruits, vegetables, and natural products such as parsley, celery, onions, leeks, broccoli, soy, oregano herbs, green tea, red wine, citrus fruit, berry fruits, and dark chocolate [20,21]. Although research has historically focused on antioxidant properties [22][23][24][25], recent data from randomized placebo-controlled trials suggest (poly)phenols may also modulate neurological disorders, cerebral hypoperfusion, and neuroinflammation while simultaneously enhancing memory, learning, and cognitive performances in old-aged adults [19,[26][27][28][29][30][31][32][33][34]. Mastroiacovo et al [26] demonstrated a daily consumption of 250 mL Cocoa drinks, with a high flavanol content (993 mg), for 8 weeks has the potential to improve psychomotor performance, verbal fluency performance, as well as the overall cognitive performance (i.e., z-score).…”
Section: Introductionmentioning
confidence: 99%
“…Small RCTs ( n = 26–37) with blueberry nutraceuticals have shown oral intake of a concentrate containing either 387 mg of anthocyanidins or 12 g of lyophilised blueberries for 12 weeks improves cognitive abilities in healthy older adults (Bowtell, Aboo‐Bakkar, Conway, Adlam, & Fulford, ; Miller, Hamilton, Joseph, & Shukitt‐Hale, ). Larger RCTs ( n = 94–122) also conclude that blueberry extracts improve memory performance in older adults when taken for periods of 3 to 6 months (McNamara et al, ; Whyte, Cheng, Fromentin, & Williams, ). Other RCTs have concluded that flavonoid‐rich citrus juices improve cognitive functions in healthy older adults ( n = 37) after 8 weeks of intake (Kean et al, ) and in healthy middle‐aged adults ( n = 22) after acute administration (Alharbi et al, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%